PENGARUH KUALITAS PRODUK, LOKASI DAN LINGKUNGAN FISIK TERHADAP PEMBELIAN ULANG PADA WARUNG KOPI HARAPAN J2 DI KOTA PALU - Yunus, Astiani (Katalogis, 2014)
The research aims are: 1) to find out the concurrent influence of Product Quality, Location and Physical Environment toward Repurchase on Harapan J2 Coffee Shop in Palu City; 2) to find out the influence of Product Quality toward Repurchase on Harapan J2 Coffee Shop in Palu City; 3) to find out the influence of Location toward Repurchase on Harapan J2 Coffee Shop in Palu City; 4) to find out the influence of Physical Environment toward Repurchase on Harapan J2 Coffee Shop in Palu City. The analysis methode utilized was multiple regression analysis with a sample size of 110 taken by porposive sampling. Based on test result it can be concluded that 1) Product Quality, Location and Physical Environment simultaneously had positive and significant influence toward Repurchase on Harapan J2 Coffee Shop; 2) Product Quality had positive and significant influence toward Repurchase on Harapan J2 Coffee Shop; 3) Location had positive and significant influence toward Repurchase on Harapan J2 Coffee Shop; 4) Physical Environment had positive and significant influence toward Repurchase on Harapan J2 Coffee Shop;